2015
DOI: 10.1007/s10072-015-2076-6
|View full text |Cite
|
Sign up to set email alerts
|

Reading beyond the glance: eye tracking in neurosciences

Abstract: From an interdisciplinary approach, the neurosciences (NSs) represent the junction of many fields (biology, chemistry, medicine, computer science, and psychology) and aim to explore the structural and functional aspects of the nervous system. Among modern neurophysiological methods that "measure" different processes of the human brain to salience stimuli, a special place belongs to eye tracking (ET). By detecting eye position, gaze direction, sequence of eye movement and visual adaptation during cognitive acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…Eye-tracking technology is one of the most commonly used techniques for measuring oculomotor behavior and, by extension, visual attention (Popa et al 2015). This type of technology helps researchers investigate the impact of various stimuli (independent variables) on the observer's eye movements (dependent variable) (Duchowski 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Eye-tracking technology is one of the most commonly used techniques for measuring oculomotor behavior and, by extension, visual attention (Popa et al 2015). This type of technology helps researchers investigate the impact of various stimuli (independent variables) on the observer's eye movements (dependent variable) (Duchowski 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The mean ITR achieved by the system was 190. 73 10 and 13)). An average spelling rate of 35.79 characters per minute (cpm) was achieved by the proposed system with maximum of 39.11 cpm.…”
Section: Online Data Analysismentioning
confidence: 96%
“…Furthermore, eye tracking-based assistive technologies are emerging as an alternative tool to BCIs [65,66]. The development of modern camera systems and the increase of computing power has enabled the gathering of eye tracking data in real time, enabling the use of gaze as a control method for people with disabilities [67][68][69][70][71][72][73]. A comparison study of BCI, eye tracking, and electrooculography interfaces reported that participants found the BCI to be the easiest to use and eye tracking to be the least tiring [65].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of professional wearable eye tracking device, such as the mobile eye from ASL [12], the SMI eye tracking glasses [13] and the Tobii pro glasses [14], the use of visual focus for behavior observation and analysis becomes possible. In fact, efforts have been made based on the eye tracking device in different areas from psychology, engineering to neuroscience [15]- [17]. From the training of marine operation perspective, eye tracking is also the important link to situation assessment of trainees.…”
Section: Introductionmentioning
confidence: 99%